Sequence characteristics and phylogenetic analysis of H9N2 subtype avian influenza A viruses detected from poultry and the environment in China, 2018 - Gao,Xiaoyi; Wang,Naidi; Chen,Yuhong; Gu,Xiaoxue; Huang,Yuanhui; Liu,Yang; Jiang,Fei; Bai,Jie; Qi,Lu; Xin,Shengpeng; Shi,Yuxiang; Wang,Chuanbin; et al. (PeerJ, 2021)
H9N2 subtype avian influenza A virus (AIV) is a causative agent that poses serious threats to both the poultry industry and global public health. In this study, we performed active surveillance to identify H9N2 AIVs from poultry (chicken, duck, and goose) and the environment of different regions in China, and we phylogenetically characterized the sequences. AIV subtype-specific reverse transcription polymerase chain reaction (RT-PCR) showed that 5.43% (83/1529) samples were AIV positive, and 87.02% (67/77) of which were H9N2 AIVs. Phylogenetic analysis revealed that all H9N2 field viruses belonged to the Y280-like lineage, exhibiting 93.9–100% and 94.6–100% of homology in the hemagglutinin (HA) gene and 94.4–100% and 96.3–100% in the neuraminidase (NA) gene, at the nucleotide (nt) and amino acid (aa) levels, respectively. All field viruses shared relatively lower identities with vaccine strains, ranging from 89.4% to 97.7%. The aa sequence at the cleavage site (aa 333–340) in HA of all the isolated H9N2 AIVs was PSRSSRG/L, which is a characteristic of low pathogenic avian influenza virus (LPAIV). Notably, all the H9N2 field viruses harbored eight glycosylation sites, whereas a glycosylation site 218 NRT was missing and a new site 313 NCS was inserted. All field viruses had NGLMR as their receptor binding sites (RBS) at aa position 224–229, showing high conservation with many recently-isolated H9N2 strains. All H9N2 field isolates at position 226 had the aa Leucine (L), indicating their ability to bind to sialic acid (SA) α, a 2–6 receptor of mammals that poses the potential risk of transmission to humans. Our results suggest that H9N2 AIVs circulating in poultry populations that have genetic variation and the potential of infecting mammalian species are of great significance when monitoring H9N2 AIVs in China.
Keywords: H9N2 subtype; Avian influenza virus; Phylogenetic analysis; Epidemiology